2023
DOI: 10.1186/s12882-023-03184-4
|View full text |Cite
|
Sign up to set email alerts
|

Update of dialysis initiation timing in end stage kidney disease patients: is it a resolved question? A systematic literature review

Abstract: Background The exact optimal timing of dialysis for ESKD patients remains unknown. This study systematically reviewed the available evidence with regard to the optimal initiation of maintenance dialysis in ESKD patients. Methods An electronic search was performed in Embase, PubMed and the Cochrane Library in order to find studies investigating associations between variables reference to “start of dialysis” and outcomes. Quality assessment and bias … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Choosing the appropriate timing of dialysis requires not only consideration of the patient's GFR, but also customization to the individual needs of the patient in terms of age, gender, comorbidities (diabetes, hypertension, etc. ), and physical condition 234–236 …”
Section: Complications Of Mnmentioning
confidence: 99%
“…Choosing the appropriate timing of dialysis requires not only consideration of the patient's GFR, but also customization to the individual needs of the patient in terms of age, gender, comorbidities (diabetes, hypertension, etc. ), and physical condition 234–236 …”
Section: Complications Of Mnmentioning
confidence: 99%
“…During its early stages, most patients remain asymptomatic, until they reach the end stage when dialysis treatments become necessary. 1 Recently studies have reported the diagnosis of CKD using relatively easily measurable urinary biomarkers such as pH and glucose 2,3 instead of the conventional analysis of glomerular filtration rate or blood albumin concentration. 4,5 However, their accurate analysis relies on sending the samples to laboratories, where dedicated equipment and skilled personnel are required.…”
Section: Introductionmentioning
confidence: 99%